Hello :
the slope of tangent in A(x':y') is : f'(x') =3
f'(x) = 2x-5
2x'-3 =3
2x' = 6
x' = 3
f(3)= 3²-5(3)+7=1
1 =3(3)+c
c =-8
Answer:
y = -3x + 2
Step-by-step explanation:
To find the slope of an equation you can do (y2-y1)/(x2-x1). Plug the values in from the equation and you get (-1+7)/(1-3), or 6/-2. This means the slope is -3. Then you plug the values of y and x into an equation y = -3x + b, and you get -1 = (-3)1 + b. Solve for b. -1 = -3 + b, (add 3 to each side) 2 = b. Then plug b back into your equation and you get y = -3x + 2
Not enough info. But assuming it’s a rectangular, area = length * width
3/4*11/12 = 33/48 = 11/16 square feet
1 feet = 30.5 centimetres
1 feet² = (30.5)² centimetres²
2250 feet² = 2250 × 30.5² = 2093062.5 centimeters²
1.8288 de diâmetro
1pés e equivalente a 0.3048 e so multiplicar por 6 que vai da 1.8288